Anxiety and locomotion in Genetic Absence Epilepsy Rats from Strasbourg (GAERS): Inclusion of Wistar rats as a second control. Issue 9 (24th July 2014) - Marques‐Carneiro, José Eduardo; Faure, Jean‐Baptiste; Cosquer, Brigitte; Koning, Estelle; Ferrandon, Arielle; de Vasconcelos, Anne Pereira; Cassel, Jean‐Christophe; Nehlig, Astrid
Summary Objective The Genetic Absence Epilepsy Rats from Strasbourg (GAERS) is a genetic model, derived from Wistar rats by selective breeding. In all previous studies, GAERS were compared to their paired selected strain not expressing spike‐and‐wave discharges (SWDs), namely nonepileptic controls (NECs). Because the occurrence/absence of SWDs is of polygenic origin, some other traits could have been selected along with occurrence/absence of SWDs. Therefore, we explored the importance of using a second control group consisting in Wistar rats, the strain of origin of GAERS, in addition to NECs, on locomotion and anxiety in GAERS. Methods A test battery encompassing home‐cage, open‐field, beam‐walking and elevated plus‐maze evaluations was used. In addition, stereologic analyses were performed to assess the volume of thalamus, amygdala, and hippocampus. The occurrence/absence of SWDs was determined in all three strains by electroencephalography (EEG) recording. Results When compared to NECs and Wistars, GAERS displayed lower exploratory activity and fastened habituation to novelty. In the plus‐maze, scores of GAERS and Wistars were similar, but NECs appeared significantly less anxious (possibly in association with increased amygdala volume); evidence for weaker anxiety in NECs was also found in the open‐field evaluation. The volumetric study revealed increased thalamic volume in GAERS compared to both control groups. SWDs were present in all GAERS and in 80% of Wistars. Significance Compared to the original Wistar strain as an additional control group, the selective breeding that generated the GAERS has no incidence on anxiety‐related behavior, conversely to the selection of SWD suppression in NECs, in which anxiety is attenuated. These findings point to the importance of using a second control group composed of Wistar rats in studies characterizing the behavioral profile of GAERS. Thereby, possible confusions between occurrence/absence of SWDs and other features that come along with selection and/or differential brain development induced by the genetic mutations are reduced.